How Social Media Marketing, Product Quality, And Brand Image Influence Millennial Purchase Intention - Ghifari Irfansyah, Muhammad Reza; Rahman, Fatchur (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
Whey Protein has become a growing trend in the health and fitness market, although it has not yet achieved a leading market position. This study aims to examine the influence of social media marketing activities, product quality, and brand image of FITlife Whey Protein on the purchase intention of millennial consumers at SAM Fitness in Malang City. Employing a quantitative descriptive approach with an explanatory research design, the study involved a population of 653 millennial consumers, from which 100 respondents were selected using a simple random sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression. The findings indicate that social media marketing activities, product quality, and brand image each have a positive and significant effect on purchase intention. The novelty of this research lies in its integrated analysis of these three factors specifically among millennial consumers. The study also highlights the strategic importance of strengthening digital marketing and maintaining high product quality to enhance consumer purchase intention.